2005
DOI: 10.1086/426444
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-Specific Early Mortality in Very Low Birth Weight Infants with Late-Onset Sepsis: A National Survey

Abstract: Klebsiella sepsis and Pseudomonas sepsis were associated with a 6.3-fold and 12.3-fold increased risk of early mortality, respectively, and accounted for 41.9% of all early deaths associated with LOS. Considering the aggressive nature of sepsis caused by these pathogens, empiric antibiotic therapy active against these organisms is worth consideration for VLBW infants with presumed LOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
71
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(86 citation statements)
references
References 22 publications
11
71
1
3
Order By: Relevance
“…As in other studies on neonatal CoNS infections that have demonstrated significant morbidity but a low rate of mortality, there were no deaths associated with SHN sepsis at our institution (15,23). The incidence and types of infection associated with SHN in hospitalized patients are not known as, like others, our laboratory does not routinely identify CoNS to the species level.…”
mentioning
confidence: 65%
“…As in other studies on neonatal CoNS infections that have demonstrated significant morbidity but a low rate of mortality, there were no deaths associated with SHN sepsis at our institution (15,23). The incidence and types of infection associated with SHN in hospitalized patients are not known as, like others, our laboratory does not routinely identify CoNS to the species level.…”
mentioning
confidence: 65%
“…There are conflicting reports as to whether this has resulted in an increase in the absolute numbers of episodes of early-onset sepsis caused by gram-negative bacteria (25,33,37), but there is evidence to suggest that antimicrobial resistance is increasing in those gram-negative isolates associated with both early-and lateonset neonatal sepsis (17,35,37). In a report from Washington, DC, 17% of infants admitted to a NICU became colonized with antibiotic-resistant Enterobacteriaceae strains, and 14% of colonized infants developed infection (36).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report from the Israeli Neonatal Network (25) estimates that sepsis due to Enterobacter spp., Escherichia spp., and Klebsiella spp. is associated with a 4.1-fold, 4.3-fold, and 6.3-fold risk of mortality, respectively, in the verylow-birth-weight population compared to that of sepsis associated with coagulase-negative staphylococci.…”
mentioning
confidence: 99%
“…eonatal bacterial sepsis, exacerbated by neonatal immunodeficiency (1), remains a major cause of mortality and morbidity in newborns (2). Vancomycin is widely used for the treatment of late-onset sepsis caused by methicillin-resistant Staphylococcus aureus and coagulase-negative staphylococci in neonatal intensive care units (NICUs) (3); however, the clinical use of vancomycin is still hampered by its narrow therapeutic index and high pharmacokinetic variability (4).…”
mentioning
confidence: 99%